The fertility of 11-12 years old frozen bull semen - ΚΑΡΑΤΖΑΣ Γ.; ΧΑΤΖΗΣ Ν. (Journal of the Hellenic Veterinary Medical Society, 2019)
Artificial insemination was performed in 34 cows of a dairy herd by using frozen semen in ampoulles from 5 bulls (selected from 450 ampoulles) stored in liquid nitrogen fro 11-12 years old. At the same time artificial insemination was also performed in 88 cows of the same herd by using bull frozen semen kept for at most one year in liquid nitrogen. A total of 14 cows of the 34 were calving (a mean proportion of 46,2%) while 59 cows from the 88 ones (a mean proportion of 68,9%). This difference is very close to be statistically significant (t=2,18 d.f. 11 ρ 0,05) of course this result has only an indicative valve since it is based on a limited number of observations. The lower percentage of the semen fertility kept 11-12 years may be attributed to nuclear activity of spermatozoa and to reduced activity of the enzymes of the cap. The percentage of the embryonic deaths in the two cases were remained low. The calves that were born from the 11-12 years old semen had normal development.